2021
DOI: 10.3389/fcell.2021.698292
|View full text |Cite
|
Sign up to set email alerts
|

3D Organoid Culture From Adult Salivary Gland Tissues as an ex vivo Modeling of Salivary Gland Morphogenesis

Abstract: Lumen formation of salivary glands has been investigated using in vivo or ex vivo rudiment culture models. In this study, we used a three-dimensional (3D) salivary gland organoid culture system and demonstrated that lumen formation could be recapitulated in mouse SMG organoids. In our organoid culture system, lumen formation was induced by vasoactive intestinal peptide and accelerated by treatment with RA. Furthermore, lumen formation was observed in branching duct-like structure when cultured in combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Previous studies by other groups have also observed dead cells and positive caspase-3 staining in the center of the acini-like structures when cultur-ing salivary gland progenitor cells in various hydrogels. [20,27,[40][41][42][43] Cavities with varying number and size were observed by day 14 (Figure 3D,E), but they cannot be designated as lumens, as it is unclear how or when they are formed and whether they are polarized differently from the outer cell layer. We speculate that cells on the inside of the spheres may undergo apoptosis because they are excluded from cell-cell contacts found on the outside of the sphere.…”
Section: Formation Of Sgm Within Hydrogel Microenvironmentsmentioning
confidence: 99%
“…Previous studies by other groups have also observed dead cells and positive caspase-3 staining in the center of the acini-like structures when cultur-ing salivary gland progenitor cells in various hydrogels. [20,27,[40][41][42][43] Cavities with varying number and size were observed by day 14 (Figure 3D,E), but they cannot be designated as lumens, as it is unclear how or when they are formed and whether they are polarized differently from the outer cell layer. We speculate that cells on the inside of the spheres may undergo apoptosis because they are excluded from cell-cell contacts found on the outside of the sphere.…”
Section: Formation Of Sgm Within Hydrogel Microenvironmentsmentioning
confidence: 99%
“…Several attempts have been conducted to fulfill these criteria (Table 2) [29,[35][36][37][38][39][40][41][42][43]. Specifically, the regulation of signaling pathways associated with SG organogenesis is one of the common strategies to improve basic culture conditions.…”
Section: Advanced Techniques For Improving the Present Sgo Culture Me...mentioning
confidence: 99%
“…In addition, chemical inhibition of activin receptor-like kinase signaling or treatment of morphogenic proteins such as the Fgf family can induce the development of acini-containing budding structure in SGOs [30,36,37]. In addition to [38] focused on recapitulating the lumen formation process during the maturation of SGOs. According to that study, the Fgf2/Fgf10 combination initiates the budding and branching elongation process, and the addition of retinoic acid (RA) enhances lumen formation within this duct-like compartment.…”
Section: Advanced Techniques For Improving the Present Sgo Culture Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel to emerging imaging technologies, efforts have been concentrated on in vitro organotypic systems of the mammary gland ( Simian et al, 2001 ; Debnath et al, 2003 ; Ewald et al, 2008 , 2012 ). Although multiple organoid models derived from different organs have achieved high levels of complexity and morphological reproducibility of in vivo structures, the complexity of murine mammary organoids is still limited ( Clevers, 2016 ; Kim et al, 2021 ; Vazquez-Armendariz and Herold, 2021 ). Current mammary organoid culture protocols result in either bi-layered sphere-shaped organoids (referred to as cysts) or budding structures upon supplementation with different growth factors, such as FGF2, FGF7, FGF10, and Neuregulin1 ( Fata et al, 2007 ; Nguyen-Ngoc et al, 2015 ; Jardé et al, 2016 ; Sumbal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%